Challenges Facing Female Headed Households in Accessing and Utilizing Microfinance Lending among Selected Municipalities of South West Uganda - Busingye, John; Kazooba, Charles Tushabomwe; Tumuhimbise, Manasseh (Basic and Applied Research, 2018)
Sub-Saharan Africa is characterized by gender inequality in the form of income, health, education, employment and human rights; suggesting that efforts aimed at reducing extreme poverty benefit males relatively more than females. Access to microfinance is one single factor identified to contribute to reduction in gender inequality. However, female headed households continue to be excluded from utilizing microfinance services either due to their relatively low income levels and lack of assets as collateral. The central question of this paper is whether increased access to microfinance leads to reduction of poverty among female headed households in selected municipalities of south west Uganda. This paper contributes to the existing literature by examining the local context faced by female headed households; in relation to ownership of household assets, health and education expenditures. The study was carried out in Mbarara and Bushenyi-Ishaka Municipalities. Data was collected from a total of 209 respondents by use of questionnaires, interviews and focused group discussions.The study reveals that female headed household face accessibility challenges like bureaucracy, limited collateral security, discrimination, loan delays and high cost of borrowing. Challenges related to loan utilization included group tension over loan repayment, loan terms, grace period, interest rates, fines and penalties. There is need for government intervention so as to embrace flexible lending policies and accommodate the gender needs and challenges of FHH borrowers. The study findings will be used by policy and development planners to redesign microfinance strategies aimed at improving the plight of the marginalized groups like women in FHH.
Keywords: Challenges; Microfinance Institutions; Female Headed Households; Poverty reduction